LOS JUDÍOS Y EL CABILDO CATEDRALICIO DE MURCIA EN EL SIGLO XV - Marsilla, Francisco (Miscelánea Medieval Murciana, 1989)
This study focuses on the participaron of the Jews in the economic activities of the Chapter of the Church in Cartagena, showing the substancial part they played in the collection of rent and general Church income troughout the Bishopric in the period in question